Faktor Pendukung dan Penghambat dalam Implementasi Program Pendaftaran Tanah Sistematis Lengkap (PTSL) Studi Kasus di Kabupaten Bantul - Enggal Suko Pangastiti; Wahyu Adi Mudiparwanto (Jurnal Hukum Lex Generalis, 2025)
The Complete Systematic Land Registration Program (PTSL) is a government effort to accelerate land registration, including in Bantul Regency. This study examines its implementation by analyzing each stage, from planning to certificate submission. The study also identified supporting factors, such as community participation and clear regulations, as well as inhibiting factors such as inherited land and disputed land. With more than 90% of land certified, PTSL has proven effective in improving land administration and legal certainty over land ownership in Bantul Regency.